Development of Pop-Up Book Media Based on Multisensory for Scientific Literacy of Early Chidhood - Vebionita Megi Putri; Yaswinda; Nenny Mahyuddin (Jurnal Ilmiah POTENSIA, 2024)
The minimal level of scientific knowledge is due to a lack of optimization of the learning process in Kindergarten. One index of the cause is that there is still little learning media for children. Developing media according to children's needs is a problem that must be solved, in order to develop children's abilities, especially scientific literacy. The aim of this research is to develop multisensory-based Pop-Up book media for early childhood science abilities. This research uses Reach and Development research which uses the development of the Borg and Gall model with 9 learning steps, namely; 1) identifying objectives with evaluation, 2) conducting learning analysis, 3) analyzing students and the learning context, 4) writing core objectives, 5) developing evaluation instruments, 6) developing learning strategies, 7) selecting and developing teaching materials, 8) designing and conducting formative learning evaluations, and 9) revising learning. Data collection techniques in this research used documentation and questionnaires. Aiken's V validation is used as a data analysis technique. The results obtained by this research are 1) lesson plan design, 2) children's conditions in the field and the problems they face, 3) child development indicators, 4) child development indicators, 5) development competencies, 6) pop-up book media development design, 7 ) media development evaluation results with a percentage of 91.25% (valid) and material media validation of 90.77% in the appropriate category (valid). An FGD was also conducted with 6 kindergarten teachers in Pasaman Regency with the results of multisensory-based pop up book media on science skills for early childhood which were appropriate (valid) and could be used in the learning process. The results of measuring children's science abilities in 3 kindergartens in Pasaman Regency which were carried out in medium classes showed that the results of the trial assessment were 87.16%, which means that children's scientific literacy abilities are developing well.